Quaternary ammonium silane-based antibacterial and anti-proteolytic cavity cleanser. Issue 12 (December 2018) - Gou, Ya-ping; Li, Ji-yao; Meghil, Mohamed M.; Cutler, Christopher W.; Xu, Hockin H.K.; Tay, Franklin R.; Niu, Li-na
Highlights: QAS cavity cleanser possesses combined antimicrobial and anti-proteolytic activities. QAS cavity cleanser does not adversely affect dentin bond strength. QAS cavity cleanser may play a role in extending the longevity of resin–dentin bonds. Abstract: Objective: Secondary caries and degradation of hybrid layers are two major challenges in achieving durable resin–dentin bonds. The objectives of the present study were to investigate the effects of a 2% quaternary ammonium silane (QAS) cavity cleanser on bacteria impregnated into dentin blocks and the gelatinolytic activity of the hybrid layers. Methods: Microtensile bond strength was first performed to evaluate if the 2% QAS cavity cleanser adversely affected bond strength. For antibacterial testing, Streptococcus mutans and Actinomyces naeslundii were impregnated into dentin blocks, respectively, prior to the application of the cavity cleanser. Live/dead bacterial staining and colony-forming unit (CFU) counts were performed to evaluate their antibacterial effects. Gelatinolytic activity within the hybrid layers was directly examined using in-situ zymography. A double-fluorescence technique was used to examine interfacial permeability immediately after bonding. Results: The cavity cleanser did not adversely affect the bond strength of the adhesives tested (p > 0.05). Antibacterial testing indicated that 2% QAS significantly killed impregnated bacteria within the dentin blocks compared with control group (p < 0.05), which was comparable with the antibacterial activity of 2% chlorhexidine (p > 0.05). Hybrid layers pretreated with 2% QAS showed significant decrease in enzyme activity compared with control group. With the use of 2% QAS, relatively lower interfacial permeability was observed, compared with control group and 2% chlorhexidine (p < 0.05). Significance: The present study developed a 2% QAS cavity cleanser that possesses combined antimicrobial and anti-proteolytic activities to extend the longevity of resin–dentin bonds.